Comparative efficacy and safety of systemic therapy for advanced hepatocellular carcinoma: a systematic review and network meta-analysis - Wu, Di; Jia, Binyang; Jia, Muyuan; Zhao, Haitao; Zhao, Hong; Zhou, Jinxue (Frontiers in Oncology, 2023)
Background: In recent years, there has been rapid development in systemic therapeutic agents for advanced hepatocellular carcinoma. However, most treatment modalities lack head-to-head comparisons, and the distinctions in their efficacy and safety have yet to be elucidated. Consequently, the accurate selection of a treatment regimen poses a significant challenge for clinicians. Methods:This study incorporated twenty-three randomized controlled trials, encompassing fifteen first-line and eight second-line treatments, and involving a total of 14,703 patients with advanced hepatocellular carcinoma. Results: In the context of first-line treatment, it was observed that the combination of a PD-1 inhibitor with bevacizumab (1/15) significantly extended overall survival in patients with advanced HCC. Furthermore, PD-1 inhibitors combined with TKIs (1/15) and PD-1 inhibitors combined with bevacizumab (2/15) exhibited enhanced efficacy in reducing the risk of progressionfree survival events. In second-line therapy, the network meta-analysis revealed that all investigational agents prolonged progression-free survival in patients with advanced hepatocellular carcinoma when compared to placebo. Cabozantinib ranked first (1/7) in this regard. However, this translated into an overall survival benefit only for cabozantinib, regorafenib, ramucirumab, and pembrolizumab, with regorafenib achieving the highest ranking (1/7). Conclusion: In the treatment of advanced HCC, the immune checkpoint inhibitor combined with bevacizumab regimen and the immune checkpoint inhibitor combined with TKI regimen stand out as the two most effective firstline treatment options. It is noteworthy that, for patients with absolute contraindications to VEGF inhibitors, dual immunotherapy is the preferred choice. For second-line treatment, regorafenib and cabozantinib are identified as the two most effective options.2 Systematic review registration: https://www.crd.york.ac.uk/prospero, identifier CRD42023440173.